Traçando Caminhos e Descaminhos de um Processo de Educação no Meio Rural: Reflexões a Partir de uma Experiência do Pronera no Rio Grande do Norte. - de Azevedo, Alessandro Augusto (Revista Entreideias: educação, cultura e sociedade, 2007)
Análise de aspectos da experiência de execução do PRONERA, através da Universidade Federal do Rio Grande do Norte. Entre as questões analisadas estão: a influência da chamada “educação bancária” entre os próprios trabalhadores e mesmo alguns monitores; as distintas visões acerca da formação pedagógica dos monitores entre universidade e movimentos sociais; e a necessidade de se fazer uma cartografia das expectativas que movem os trabalhadores rurais ao envolvimento em programas dessa natureza. Alguns elementos da análise foram recolhidos durante as visitas, reuniões e seminários de formação pedagógica, como também através de uma pesquisa entre os próprios trabalhadores, nos assentamentos. Palavras-chave: Educação popular; meio rural; projeto político-pedagógico. Abstract: Education in rural midst: reflection about experience done by PRONERA in Rio Grande do Norte. Analysis of some aspects of execution of National Program of education experience in Agrarian Reform in Rio Grande do Norte, through Federal University of Rio Grande do Norte. The subjected aspects link up as query and reflection about some parameter theorical-philosophical that perspectives are basics of various agents that participated of pedagogical process and support of implicit model the really politic-pedagogical project executed in the program. Among the analyzed questions are: the called “banking education” influence between the own workers and even some pedagogical monitors instruction between social movement and university, and the necessity of to do one cartography expectation that move rural workers to the program envelopment in this nature. Some element of analyses was gathered during visit, meeting and pedagogical form seminaries as also through own workers research in the laying. Key words: Young and adults education, rural midst, and politic-pedagogical project.